Concept of Kala-Prakarsha in Ayurveda - Dwivedi, Mohan Krishna (International Journal of Pharmaceutical & Biological Archive, 2017)
Every matter undergoes a change with time that is considered as Parinama (outcome) in Ayurveda. When this time is protracted in such a way, that these outcome cultivates a fruitful result under some specific conditions, it is known as Kala-Prakarsha or it can be said that Kala becomes Kala-Prakarsha. Kala-Prakarsha is also one of the major Samskara responsible for transformation having its utility in almost all pharmaceutical processings. Ayurveda advocates certain procedures like Kala-Prakarsha (curing) for certain drugs before their administration. Bhallataka (Semecarpus anacardium Linn.) is one such drug, which is to be processed through curing procedure. There are several examples available in classical texts about Kala-Prakarsha whereby applying this Samskara, enhancement of the drug potency is achieved. Considering this, it is planned to evaluate most of the examples present in texts by which exploration of different procedures of drug potency advancement can be elucidated.